Solving ethical dilemmas in international healthcare professional education: A case study using a revised ethical model in East Africa - Kate Thomas; James Smith; J Dwight Phillips; Shari Falkenheimer (Health for All Nations, 2018)
Ethical issues frequently arise during the practice of clinical medicine and when providing medical education. These issues become particularly challenging when practicing and teaching medicine cross-culturally. In this case study in a family medicine residency program in East Africa, a structured approach to managing ethical challenges effectively was found to assist in overcoming a conflict about potentially removing a seemingly incompetent medical trainee from a residency program. The step-wise approach includes identifying relevant stakeholders; agreeing on actual background facts; understanding the various goals and values involved in the situation; reviewing locally applicable ethical, professional and legal standards; acknowledging limitations in various options to resolve the issues; and analyzing risks and benefits of the various courses of action.